Skema Citra Ruang pada Ungkapan Metaforis dalam Novel Laut Bercerita Karya Leila S. Chudori: Kajian Semantik Kognitif - Putri, Laily Adha Intan; Nur, Tajudin (Humanis; Vol 28 No 3 (2024), 2024)
This research aims to describe the spatial image schemas in metaphorical expressions in the novel Laut Bercerita by Leila S. Chudori. Previous research has mostly analyze metaphors based on types of space, so research on types of image schemes has not been studied much. The research method is descriptive qualitative. Data was collected using the observation method with close reading techniques, then analyzed using the distributional method. The theory used image schema according to Croft and Cruse (2004) and metaphor according to Lakoff and Johnson (2003). The results of the research show that the spatial image scheme in the novel Laut Bercerita consists of top-bottom, near-far, and center-surround spatial image schemes. All data includes a type of orientational metaphor because orientational metaphor is closely related to the spatial image scheme. The spatial image scheme is spatially oriented, as is the characteristic of orientational metaphor. Therefore, the type of metaphor with a spatial image scheme is an orientational metaphor.